On Referential Distance in Written Texts - Novaković, Jelena Š.; PhD Cand. Božana Tomić, (European Journal of Multidisciplinary Studies, 2017)
Apart from personal pronouns which are by far the most used referring expressions in English and Serbian, reference can be established and maintained using demonstratives. Their function is to refer to the location or distance of a person or an object. The aim of this paper is to examine reference realised by demonstratives with special regard to the restrictions written discourse imposes on their usage. The texts we used for analysis are narrative stories written in the two languages.
Keywords: demonstratives, reference, restrictions, English, Serbian.